sEMG Activities of the Three Heads of the Triceps Brachii Muscle During Cricket Bowling - Ali, Md. Asraf; Sundaraj, Kenneth; R. Badlishah, Ahmad; Ahamed, Nizam Uddin; Islam, Md. Anamul; Sundaraj, Sebastian (World Scietific, 2016)
The aim of the present study was to analyze the surface electromyography (sEMG) activities generated by the three heads of the triceps brachii (TB) muscle among the different phases during fast and spin bowling. sEMG signals from the lateral, long and medial heads of the TB from 20 bowlers were measured individually during bowling. To analyze the sEMG activities, the root mean square (RMS) value in each bowling phase for every trial per bowler was calculated from the sEMG signals from the three heads of the TB. Higher sEMG activities at the three heads of the TB were found during the fifth phase followed by the sixth, seventh, third, fourth, second and first phases in both types of bowling. sEMG activities were significantly different among the three heads of the TB and among the seven bowling phases for both bowling types at an alpha level of p<0.05.These findings will be of particular importance for assessing different physical therapies for the three headed TB muscle which can improve the performance in ball delivery of cricket bowlers.